Scalp and Intracranial EEG in Medically Intractable Extratemporal Epilepsy with Normal MRI. (25th June 2012) - Zakaria, Tarek; Noe, Katherine; So, Elson; Cascino, Gregory D.; Wetjen, Nicholas; Van Gompel, Jamie J.; Marsh, W. Richard; Meyer, Fredric Bruce; Giannini, Caterina; Watson, Robert E.; Worrell, Gregory A.
Abstract : Purpose . To investigate EEG and SPECT in the surgical outcome of patients with normal MRI (nonlesional) and extratemporal lobe epilepsy. Methods . We retrospectively identified 41 consecutive patients with nonlesional extratemporal epilepsy who underwent epilepsy surgery between 1997 and 2007. The history, noninvasive diagnostic studies (scalp EEG, MRI, and SPECT) and intracranial EEG (iEEG) monitoring was reviewed. Scalp and iEEG ictal onset patterns were defined. The association of preoperative studies and postoperative seizure freedom was analyzed using Kaplan-Meier analysis, log-rank test, and Cox proportional hazard. Results . Thirty-six of 41 patients had adequate information with a minimum of 1-year followup. Favorable surgical outcome was identified in 49% of patients at 1 year, and 35% at 4-year. On scalp EEG, an ictal onset pattern consisting of focal beta-frequency discharge (>13–125 Hz) was associated with favorable surgical outcome (P = 0.02 ). Similarly, a focal fast-frequency oscillation (>13–125 Hz) on iEEG at ictal onset was associated with favorable outcome (P = 0.03 ). Discussion . A focal fast-frequency discharge at ictal onset identifies nonlesional MRI, extratemporal epilepsy patients likely to have a favorable outcome after resective epilepsy surgery.